The return or the three faces of Europe - Šola, Tomislav (2006)
The period after 1989 has introduced new opportunities and challenges for the rich, multicultural heritage of Central Europe. Heritage has become not only a national treasure and the basis for identity building but also a market commodity used and exploited by many different actors. This unique historical experience, combining both the fall of communism and political and economic transformation is worth presenting in an international context and can enrich the global discussion about the understanding of heritage and its usage.
Projekt MZOS
ENG